Handwashing among Schoolchildren in Jatinangor, West Java - Cheryl May Chong Sue Faye; Chrysanti Chrysanti; Sharon Gondodiputro (Althea Medical Journal, 2016)
Background: Diarrhea and pneumonia accounts for an estimated 40% of all child deaths around the world each year. Handwashing with soap could protect about 1 out of every 3 young children who get sick with diarrhea and almost 1 out of 6 young children with respiratory infections like pneumonia. Although people around the world clean their hands with water, very few use soap to wash their hands. Washing hands with soap removes germs much more effectively. This study was undertaken to determine the level of knowledge and practice regarding proper handwashing among elementary school children.Methods: A descriptive study was conducted from August to October 2014 in Jatinangor using primary data from respondents who are 5th graders from four schools. A total of 49 males and 50 females were chosen using cluster random sampling. Schoolchildren who were present, able and well were given questionnaires after written informed consent was obtained from the schoolchildren and their guardians. Then, respondents demonstrated hand-washing techniques which were evaluated using a checklist.Results: Overall, 52% of the schoolchildren had moderate level of hand washing knowledge and 66% had bad handwashing practices.Conclusions: Despite having a moderate level of handwashing knowledge, the majority still had poor handwashing practices. Handwashing programs should be carried out extensively to improve knowledge and practice.[AMJ.2016;3(2):170–4]DOI: 10.15850/amj.v3n2.795